Analyzing Financial Management and Investment Feasibility of MIXUE Beverage Franchise in Indonesia - Giawa, Erniman; Palupiningtyas, Dyah (Universitas Sains dan Teknologi Komputer, 2026)
The rapid growth of beverage franchises in Indonesia, particularly MIXUE with over 4,000 outlets, necessitates an in-depth examination of the financial management strategies underlying its success. This study aims to analyze the effects of working capital management, supply chain support, and operational cost efficiency on financial performance, as well as to evaluate the investment feasibility of the MIXUE franchise in Indonesia. A mixed-methods sequential explanatory approach was employed, utilizing multiple regression analysis and capital budgeting methods including Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Return on Investment (ROI). Data were collected from 50 franchise outlets across Jakarta, Bandung, Surabaya, and Semarang during 2022-2024, supplemented by in-depth interviews with 15 franchisees and 3 regional managers. Results reveal that all three independent variables significantly and positively affect financial performance: working capital management (β = 0.412; p = 0.002), supply chain support (β = 0.358; p = 0.008), and operational cost efficiency (β = 0.486; p < 0.001) with R² = 0.684. Investment feasibility analysis indicates an average positive NPV of IDR 290.1 million, IRR 36.5%, PP 22.2 months, and ROI 56.5%. This study contributes novel insights by integrating financial and supply chain analysis within the context of beverage franchising in emerging Asian markets, providing a comprehensive evaluation framework for prospective investors and franchise system developers.